The dilemma of choosing a distribution route : a case study of Wyeth Limited-India - Acharya, Nabajyoti; Shankar, Ravi; Sununta Siengthai; Winai Wongsurawat; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
The efforts of serving the target customers at their right place and right moments had been a traditional practice of each successful business. Every customer wants to find their needs in best possible price and quantity Iquality within their convenient locality. This has become the basic framework of modem retail industry. This study had been done to understand how a global player face challenges in an emerging market in many distribution as well as promotional issues. The global strategies of the company may not be equally effective in such markets. A case study had been picked up to find out favorable solutions of the dilemma of global player while launching a range of nutritional products with some legal constrains. It become a critical situation when the company enters an emerging market with new product lines but they can't promote it commercially due to legal constrains in the promotion of the particular category of the product. Wyeth Limited is globally well-known as a drug maker, but they have also a business of nutritional products. They faced a dilemma in choosing the right distribution route to cater the Indian market. This study had been conducted to analyze Wyeth's strategic situation considering the proposal to launch their nutritional ranges of products. A structured interview had been conducted to collect few primary data directly from the market.
A project submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Project (M.B.A.) - Asian Institute of Technology, 2008
Keywords: Wyeth Limited, India; Drugs -- India -- Makarting